Contribution of Gulf of Aqaba Water (GAW) to Red Sea waters - Wafar, Mohideen (Sustainable Marine Structures, 2020)
Data obtained on hydrography and currents in meridional sections in the Gulf of Aqaba and the Red Sea in November 2013 and March 2015 were used to determine the extent of contribution of Gulf of Aqaba Water (GAW) to the formation of Red Sea waters. The southward flow across the Strait of Tiran was ~0.02 Sv in both periods which is direct evidence of significant contribution of GAW to Red Sea waters in autumn-winter. A multiple tracer analysis using temperature, salinity, and dissolved oxygen showed that the GAW, on entry into Red Sea, bifurcates into two branches. The upper branch exiting the Strait in the depth range 150-220 m has densities between 28.3 and 28.5, continues to flow at the same depths, and feeds the Red Sea Overflow Water (RSOW). The lower branch that exits between 220 and 250 m above the sill cascades down its southern face, mixes with northward recirculating branch of Red Sea Deep Water (RSDW) and sinks to the bottom and forms part of southward-flowing RSDW. Contribution of GAW to northern Red Sea waters below 100 m depth was 36 ± 0.4% in November 2013 and 42.1 ± 5.4% in March 2015. GAW is traceable down to 17-19 °N in RSDW and RSOW. Volume contribution of GAW to RSOW was 9.6 * 1012 m3, about 50% higher than that for RSDW (6 * 1012 m3). Analyses of the data from R.V. Maurice Ewing cruise in 2001 gave similar results and lend support for these deductions. ER